Gastroenteropancreatic neuroendocrine tumours (GEP-NET) – Imaging and staging. Issue 1 (January 2016) - Baumann, Tobias; Rottenburger, Christof; Nicolas, Guillaume; Wild, Damian
Abstract : Detection of gastroenteropancreatic neuroendocrine tumours (GEP-NETs) and monitoring of treatment response relies mainly on morphological imaging such as computed tomography (CT) and magnetic resonance imaging (MRI). Molecular imaging techniques also in combination with CT (hybrid imaging) greatly benefit patient management, including better localization of occult tumours and better staging. Somatostatin receptor scintigraphy (SRS) and somatostatin receptor (SSTR) positron emission tomography (PET) play a central role in the diagnostic work-up of patients with well-differentiated GEP-NETs. SSTR PET/CT is superior to SRS and should be used whenever available. 18 F-DOPA and 18 F-FDG PET/CT is inferior to SSTR PET/CT at least in patients with well-differentiated GEP-NETs. Both SSTR PET/CT and SRS have limitations, such as relatively low detection rate of benign insulinomas, poorly differentiated GEP-NETs and liver metastases. New innovations such as SSTR PET/MRI, radiolabelled SSTR antagonists and glucagon-like peptide-1 receptor (GLP-1R) agonists might further improve imaging of GEP-NETs.